Characterization of grapevine wood microbiome through a metatranscriptomic approach - Paolinelli, Marcos; Escoriaza, Maria Georgina; Cesari, Cecilia Alicia; Garcia Lampasona, Sandra Claudia; Hernandez Martinez, Rufina (Springer, 2021)
Grapevine trunk diseases threaten wine and table grape production worldwide, primarily by reducing yields and, in its advanced stages, causing plant death. Among those diseases, the complex etiology disease known as hoja de malvón (HDM) significantly concerns Argentinian and Uruguayan viticulture. At least four different fungi are associated with this disease, but their role and interactions with other wood microorganisms are understudied. In this sense, analyzing grapevine wood microbiome composition could help understand microbial interactions occurring in HDM onset. Hence, a metatranscriptomic study was performed for the microbiome characterization of mature field-grown Vitis vinifera cv. Malbec, leaf-symptomatic or leaf-asymptomatic. The microbiome was mainly represented by Dothideomycetes and Actinobacteria. In the plant with more marked symptoms, higher levels of the Basidiomycota Arambarria destruens and Phellinus laevigatus were detected. Despite this particular difference, discriminating symptomatic from asymptomatic plants based on the presence or abundance of HDM pathogens was not possible. Alpha diversity and rank-abundance curve analyses indicated that plants with foliar symptoms have lower microbial evenness than asymptomatic plants. The co-occurrence network modeled microbial interkingdom interactions. Molecular data generated in this study will help develop future targeted molecular quantification for specific taxa.